The Project Development of Administrative Processes Reengineering Within the Public Authorities - D. Yu. Ivanov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
In this article is considered the possibility and expediency of methods application of Business Process Re-engineering for increase of activity efficiency of public authorities. The activities of public authorities are based on a process approach, according to which there is a variety of functions of public administration and the provision of public services to organizations and citizens. A significant number of administrative regulations contain a large number of processes that generate a number of additional procedures and actions of employees to perform them. To improve the efficiency of administrative processes in the public authorities it is proposed to use the methodology of Business Process Re-engineering (BPR), which has proved its effectiveness in the implementation of projects of restructuring of management systems of a significant number of commercial organizations. The article deals with the method of development and subsequent implementation of the administrative processes reengineering project in the executive bodies of public authorities.